Origins of Exploitation and Class: Value Theory of Pre-Capitalist Economy - Roemer, John E. (Econometrica, 1982)
Both the class position of agents and their status as exploiters or exploited is endogenously determined as they optimize against asset constraints which limit their capacity to produce revenue. The Class Exploitation Correspondence Principle (CECP) asserts that class and exploitation status are related in a classical way. It is further shown that the class structure associated with a labor market can be generated isomorphically by a credit market, demonstrating the functional equivalence of these markets. Morever, these results hold in models of precapitalist, subsistence economy, showing that the phenomena of Marxian exploitation and class are applicable in economic mechanisms other than capitalist ones. The possibility for a general theory of exploitation is thereby suggested.